2014
DOI: 10.1371/journal.pone.0096902
|View full text |Cite|
|
Sign up to set email alerts
|

The Cost and Impact of the Interim Federal Health Program Cuts on Child Refugees in Canada

Abstract: IntroductionOn June 30, 2012, Interim Federal Health Program (IFHP) funding was cut for refugee claimant healthcare. The potential financial and healthcare impacts of these cuts on refugee claimants are unknown.MethodsWe conducted a one-year retrospective chart review spanning 6 months before and after IFHP funding cuts at The Hospital for Sick Children, a tertiary care children's hospital in Toronto. We analyzed emergency room visits characteristics, admission rates, reasons for admission, and financial recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…This confusion may lead to refusal of services to individuals with valid IFH coverage, requesting payment for services to which they are entitled or discouraging clinicians from providing services. Indirect negative consequences are also to be expected as refusal of care and demands of fees may deter refugee claimants from seeking health care in the future [ 9 , 17 ]. Poor knowledge uptake concerning the IFH program may be linked to an overly complex program, poorly designed implementation procedures, inadequate dissemination of information, and/or the target audience’s lack of interest (for example, busy physicians who experience difficulties being reimbursed may choose to refuse IFH patients rather than seeking additional information)[ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This confusion may lead to refusal of services to individuals with valid IFH coverage, requesting payment for services to which they are entitled or discouraging clinicians from providing services. Indirect negative consequences are also to be expected as refusal of care and demands of fees may deter refugee claimants from seeking health care in the future [ 9 , 17 ]. Poor knowledge uptake concerning the IFH program may be linked to an overly complex program, poorly designed implementation procedures, inadequate dissemination of information, and/or the target audience’s lack of interest (for example, busy physicians who experience difficulties being reimbursed may choose to refuse IFH patients rather than seeking additional information)[ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study describes the impact of the 2012 cuts to the IFH program on ED use by adult refugee claimants. Evans et al published a similar study in 2014 on the impact of the cuts on claims made in the pediatric ED at the Hospital for Sick Children in Toronto [ 15 ]. Similar to our study, they found that the IFH program cuts, reduced the number of claims and increased rejected claims.…”
Section: Discussionmentioning
confidence: 99%
“…A one-year retrospective chart review study examining emergency room visits at the Hospital for Sick Children in Toronto six months before and six months following the IFHP cuts determined that the hospital was unable to obtain federal health coverage for the vast majority of refugee claimant children registered under the IFHP, and that the costs were absorbed by the hospital (Evans et al 2014). The question of how the reforms impacted Canadian politics is as yet unstudied.…”
Section: Discussionmentioning
confidence: 99%